Intranasal Vaccination with an Engineered Influenza Virus Expressing the Receptor Binding Subdomain of Botulinum Neurotoxin Provides Protective Immunity Against Botulism and Influenza - Li, Junwei; Diaz-Arévalo, Diana; Chen, Yanping; Zeng, Mingtao (Frontiers in Immunology, 2015)
Influenza virus is a negative, segmented RNA virus without DNA intermediate. This makes it safer as a vaccine delivery vector than most DNA viruses that have potential to integrate their genetic elements into host genomes. In this study, we developed a universal influenza viral vector, expressing the receptor binding subdomain of botulinum neurotoxin A (BoNT/A).We tested the growth characters of the engineered influenza virus in chicken eggs and Madin-Darby Canine Kidney epithelial cells (MDCK), and showed that it can be produced to a titer of 5×10E6 plaque forming unites/ml in chicken eggs and MDCK cells. Subsequently, mice intranasally vaccinated with the engineered influenza virus conferred protection against challenge with lethal doses of active BoNT/A toxin and influenza virus. Our results demonstrated the feasibility to develop a dual purpose nasal vaccine against both botulism and influenza.